Antibacterial Activities of Essential Oil and Composition of Stachys acerosa Boiss. - MH Moshafi; A Mofidi; M Mehrabani; M Mehrabani (Institue of Medicinal Plants, ACECR, 2010)
Background: Stachys acerosa Boiss (Lamiaecae) is an endemic plant of Iran. Objective: Because there is no report about this plant and according to medicinal uses of another species of Stachys, in this investigation, chemical composition and antimicrobial acivity of essential oils of flowering and non flowring tops of S. acerosa were studied and the component with antimicrobial activity was identified. Methods: Flowering and non flowering tops of the plant were collected from Lalehzar (Kerman provience) and after drying their essential oils were obtained by Clevenger apparatus. The oils were analyzed by GC-MS apparatus and retention indices. Antimicrobial activities of essential oils against Staphylococcus aureus, S. epidermidis, Eshrichia coli, Bacillus subtillis, Kelebsiella pneumonia and Pseudomonas aeroginosa were investigated by bioautography method on silica gel GF254 TLC plates developed in toluene: ethyl acetate (93:7). Results: Flowering and non flowering plants yielded 0.09% and 0.11% (v/w) of clear yellowish essential oil and chrysanthenyl acetate and linalool as were major constituents respectively. Most anitimicrobial activities, detected by TLC, showed in Rf=0.5-0.6 in essential oil of non flowering tops and after extraction of this fraction from preparative TLC and GC-MS analysis, it showed that Carvacrol was the major compound. Conclusion: There are reports about antimicrobial activities of other Stachys species, and chrysanthenyl acetate and linalool as major constituents of essential oils in other species of Stachyes.